New Insights into Systemic Sclerosis - Tomcik, Michal (IntechOpen, 2019)
Systemic sclerosis (scleroderma) is an incurable connective tissue disease of unknown etiology. Three key processes play a pivotal role in the pathogenesis: immune dysregulation and inflammation, endothelial injury and vasculopathy, and fibrosis. Tissue fibrosis is the dominant and characteristic feature that affects the skin and visceral organs. Life expectancy of scleroderma patients has improved over recent years, mainly because of better treatment of organ involvement and complications; however, no curative disease-modifying therapies exist to date. This book aims to provide students, trainees, rheumatologists, and other specialists interested in this disease with a comprehensive overview of novel pathogenetic mechanisms, management approaches, and therapeutic targets of several major vascular and fibrotic manifestations, and is useful insight into a number of usually neglected aspects of scleroderma.